Nerve Decellularized Matrix Composite Scaffold With High Antibacterial Activity for Nerve Regeneration - Kong, Yan; Wang, Di; Wei, Qufu; Yang, Yumin (Frontiers in Bioengineering and Biotechnology, 2022)
Nerve decellularized matrix (NDM) has received much attention due to its natural composition and structural advantages that had proven to be an excellent candidate for peripheral nerve regeneration. However, NDM with simultaneous biocompatibility, promoting nerve regeneration, as well as resistant to infection was rarely reporter. In this study, a porous NDM-CS scaffold with high antimicrobial activity and high biocompatibility was prepared by combining the advantages of both NDM and CS in a one-step method. The NDM-CS scaffold possessed high porosity and hydrophilicity, exhibited excellent biocompatibility which was suitable for cell growth and nutrient exchange. Meanwhile, NDM-CS scaffold had a significant antibacterial effect on both E. coli and S. aureus, which could avoid wound infection during the repair process. In addition, the NDM-CS scaffold could support the growth and viability of Schwann cells effectively. Among them, the E2C1 group had the strongest ability to enhance proliferation, polarization and migration of Schwann cells among the three groups. The positive effect on Schwann cells indicated their ability in the process of nerve injury repair. Therefore, this NDM-CS scaffold may have potential prospects for application in neural tissue engineering.